Identifikasi Senyawa Metabolit Sekunder Pada Jantung Pisang Kapas (Musa x paradisiaca L.) - Yogi Fernanda Saputra; Sri Benti Etika; Melindra Mulia (Jurnal Periodic Jurusan Kimia UNP, 2022)
Musa x paradisiaca L. or cotton banana is a plant that belongs to the Musaceae family. Almost all parts of this plant can be consumed, one of which is the banana blossom. Banana blossom can be cooked as a vegetable and is useful in treating diabetes. In this study, phytochemical screening was carried out to determine secondary metabolites contained in Musa x paradisiaca L. The results of phytochemical screening showed that Musa x paradisiaca L. contained secondary metabolites of flavonoids, terpenoids, phenolics and saponins, but did not contain alkaloids and steroids.